Atomic Force and Scanning Tunneling Microscopy of Ordered Ionic Liquid Wetting Layers from 110 K up to Room Temperature - Meusel, Manuel; Lexow, Matthias; Gezmis, Afra; Schötz, Simon; Wagner, Margareta; Bayer, Andreas; Maier, Florian; Steinrück, Hans-Peter (ACS nano, 2020)
Ionic liquids (ILs) are used as ultrathin films in many applications. We studied the nanoscale arrangement within the first layer of 1,3-dimethylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([C1C1Im] [Tf2N]) on Au(111) between 400 and 110 K in ultrahigh vacuum by scanning tunneling and noncontact atomic force microscopy with molecular resolution. Compared to earlier studies on similar ILs, a different behavior is observed, which we attribute to the small size and symmetrical shape of the cation: (a) In both AFM and STM only the anions are imaged; (b) only long-range-ordered but no amorphous phases are observed; (c) the hexagonal room-temperature phase melts 30-50 K above the IL's bulk melting point; (d) at 110 K, striped and hexagonal superstructures with two and three ion pairs per unit cell, respectively, are found. AFM turned out to be more stable at higher temperature, while STM revealed more details at low temperature.
CRIS-Team Scopus Importer:2020-08-28
Keywords: atomic force microscopy (AFM); Au(111); interface; ionic liquids (ILs); scanning tunneling microscopy (STM)

CO Permeability and Wetting Behavior of Ionic Liquids on Pt(111): An IRAS and PM-IRAS Study from Ultrahigh Vacuum to Ambient Pressure - Blaumeiser, Dominik; Schuschke, Christian; Fromm, Lukas; Taccardi, Nicola; Schötz, Simon; Eschenbacher, Roman; Bühlmeyer, Hanna; Xu, Tao; Bauer, Tanja; Wasserscheid, Peter; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry C, 2021)
Solid catalysts with ionic liquid layers (SCILLs) show improved performance as compared to ionic liquid (IL)-free catalysts. To realize the beneficial IL-induced modification, the IL layer should be stable under reaction conditions but also permeable for gaseous reactants entering through the IL phase. Herein, we applied (polarization modulation-) infrared reflection absorption spectroscopy ((PM-)IRAS) to investigate the CO permeability of model SCILL systems. We investigated three different IL model systems prepared by physical vapor deposition (PVD) in ultrahigh vacuum (UHV) on atomically clean Pt(111), namely, 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ([C4C1Pyr][NTf2]), 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2C1Im][NTf2]), and 1-butyl-1-methylpyrrolidinium trifluoromethanesulfonate ([C4C1Pyr][OTf]). The adsorption geometries of the anions depend on the surface structure, IL coverage, and precoverage of CO. At room temperature, IL multilayers of randomly oriented species grow on top of strongly adsorbed wetting layers. Upon heating, a partial wetting transition induces the coexistence of an IL wetting monolayer film with three-dimensional droplets. Gas-phase CO does not permeate through IL multilayers, while it penetrates the IL wetting monolayer leading to mixed IL/CO films. The partial dewetting transition and the permeability differ drastically with the temperature and IL. Consequently, the morphology of the IL films could be a factor that determines the catalytic behavior of SCILLs to a significant extent.
CRIS-Team Scopus Importer:2021-08-06

Enhancing the feasibility of Pd/C-catalyzed formic acid decomposition for hydrogen generation - catalyst pretreatment, deactivation, and regeneration - Kosider, Axel; Blaumeiser, Dominik; Schötz, Simon; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter; Libuda, Jörg; Bauer, Tanja (Catalysis: Science and Technology, 2021)
Formic acid decomposition (FAD) generates H-2 at low temperatures. However, many known catalyst systems suffer from deactivation due to competing side reactions during FAD. In this work, we focus on the origins of the deactivation of Pd catalysts but also on protocols which allow for reactivation of this precious metal catalyst. We combined batch experiments with results from in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). We find that CO adsorbates block catalytic sites and deactivate the Pd catalyst. Oxidative treatment lifts this inhibition. Additionally, our results show that oxidative pretreatment activates the Pd catalyst, whereas reduction leads to a catalyst which is essentially inactive for FAD.
CRIS-Team WoS Importer:2021-05-28

Growth and stability of Pt nanoclusters from 1 to 50 atoms on h-BN/Rh(111) - Düll, Fabian; Meusel, Manuel; Späth, Florian; Schötz, Simon; Bauer, Udo; Bachmann, Philipp; Steinhauer, Johann; Steinrück, Hans-Peter; Bayer, Andreas; Papp, Christian (Physical Chemistry Chemical Physics, 2019)
The h-BN nanomesh on Rh(111) is used as eggbox-like template for the formation of arrays of Pt nanoclusters with a narrow size distribution. Nanoclusters with sizes from 1 up to 50 atoms are prepared simultaneously in a wedge-like structure by depositing a coverage gradient on the h-BN nanomesh, and thus can be investigated under identical conditions. We studied the preparation and properties of these Pt nanoclusters of different size in situ by high-resolution X-ray photoelectron spectroscopy and scanning tunneling microscopy. For a Pt coverage of 0.1 ML, all pores of the h-BN nanomesh are filled with nanoclusters with a remarkably uniform cluster size of ≈12 Pt atoms per pore, and high stability up to 400 K. Above 0.2 ML Pt, the clusters are less stable. The coverage dependent analysis shows that for Pt coverages below 0.1 ML, the number of nanoclusters is smaller - and the number of empty pores higher - than expected for a simple hit and stick mechanism. We assign this behavior to an initially higher mobility of the Pt atoms in a hot precursor state.
CRIS-Team Scopus Importer:2019-10-11

Hydrogen Production Based on Liquid Organic Hydrogen Carriers through Sulfur Doped Platinum Catalysts Supported on TiO2 - Chen, Ximeng; Gierlich, Christian H.; Schötz, Simon; Blaumeiser, Dominik; Bauer, Tanja; Libuda, Jörg; Palkovits, Regina (ACS Sustainable Chemistry & Engineering, 2021)
In order to move from a carbon-based energy system to a more sustainable one, focus is put on liquid organic hydrogen carrier (LOHC) systems for CO2-free hydrogen storage and release. In this study sulfur as a dopant for the Pt/TiO2 catalyst was identified to be a selective poison resulting in high performing catalysts in the dehydrogenation experiments with the LOHC system perhydro dibenzyltoluene/dibenzyltoluene (H18-DBT/H0-DBT). The Pt/TiO2 and S-Pt/TiO2 catalysts were compared to the current benchmarks Pt/γ-Al2O3 and S-Pt/γ-Al2O3. S-Pt/TiO2 was found to achieve a high degree of dehydrogenation of 98% which is competitive to the benchmark S-Pt/γ-Al2O3. In addition, analyses of the side products resulted in a higher selectivity toward dibenzyltoluene for S-Pt/TiO2 than for the γ-Al2O3 supported catalysts. Characterization with infrared spectroscopy (IR), transmission electron microscopy (TEM), and diffuse reflectance infrared Fourier transform spectroscopy with CO as adsorbing molecule (CO-DRIFTS) suggest the presence of strongly chemisorbed sulfur species as well as SMSI effects of the Pt/TiO2 catalysts. Based on kinetic studies, a batch and plug flow reactor for the dehydrogenation reaction were simulated for both titania supported catalysts. According to the calculations, the sulfur doped catalyst displays higher conversions in both batch and plug flow operation as compared to the unmodified system Pt/TiO2.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Catalytic dehydrogenation; Dibenzyltoluene; Liquid organic hydrogen carrier; Perhydro dybenzyltoluene; Reversible hydrogen storage; Selective poisoning

Improving the Performance of Supported Ionic Liquid Phase Catalysts for the Ultra-Low-Temperature Water Gas Shift Reaction Using Organic Salt Additives - Wolf, Patrick; Wick, Christian; Mehler, Julian; Blaumeiser, Dominik; Schötz, Simon; Bauer, Tanja; Libuda, Jörg; Smith, David M.; Smith, Ana-Suncana; Haumann, Marco (ACS Catalysis, 2022)
The water gas shift reaction (WGSR) is catalyzed by supported ionic liquid phase (SILP) systems containing homogeneous Ru complexes dissolved in ionic liquids (ILs). These systems work at very low temperatures, that is, between 120 and 160 °C, as compared to >200 °C in the conventional process. To improve the performance of this ultra-low-temperature catalysis, we investigated the influence of various additives on the catalytic activity of these SILP systems. In particular, the application of methylene blue (MB) as an additive doubled the activity. Infrared spectroscopy measurements combined with density functional theory (DFT) calculations excluded a coordinative interaction of MB with the Ru complex. In contrast, state-of-the-art theoretical calculations elucidated the catalytic effect of the additives by non-covalent interactions. In particular, the additives can significantly lower the barrier of the rate-determining step of the reaction mechanism via formation of hydrogen bonds. The theoretical predictions, thereby, showed excellent agreement with the increase of experimental activity upon variation of the hydrogen bonding moieties in the additives investigated.
CRIS-Team Scopus Importer:2022-06-03
Keywords: electronic interaction; methylene blue; ruthenium; supported ionic liquid phase; water gas shift reaction

Metal-Support Interaction and Charge Distribution in Ceria-Supported Au Particles Exposed to CO - Bezkrovnyi, Oleksii; Bruix, Albert; Blaumeiser, Dominik; Piliai, Lesia; Schötz, Simon; Bauer, Tanja; Khalakhan, Ivan; Skala, Tomas; Matvija, Peter; Kraszkiewicz, Piotr; Pawlyta, Miroslawa; Vorokhta, Mykhailo; et al. (Chemistry of Materials, 2022)
Understanding how reaction conditions affect metal-support interactions in catalytic materials is one of the most challenging tasks in heterogeneous catalysis research. Metal nanoparticles and their supports often undergo changes in structure and oxidation state when exposed to reactants, hindering a straightforward understanding of the structure-activity relations using only ex situ or ultrahigh vacuum techniques. Overcoming these limitations, we explored the metal-support interaction between gold nanoparticles and ceria supports in ultrahigh vacuum and after exposure to CO. A combination of in situ methods (on powder and model Au/CeO2 samples) and theoretical calculations was applied to investigate the gold/ceria interface and its reactivity toward CO exposure. X-ray photoelectron spectroscopy measurements rationalized by first-principles calculations reveal a distinctly inhomogeneous charge distribution, with Au+ atoms in contact with the ceria substrate and neutral Au0 atoms at the surface of the Au nanoparticles. Exposure to CO partially reduces the ceria substrate, leading to electron transfer to the supported Au nanoparticles. Transferred electrons can delocalize among the neutral Au atoms of the particle or contribute to forming inert Au- atoms near oxygen vacancies at the ceria surface. This charge redistribution is consistent with the evolution of the vibrational frequencies of CO adsorbed on Au particles obtained using diffuse reflectance infrared Fourier transform spectroscopy.
CRIS-Team Scopus Importer:2022-09-16

Molecular and Structural Insights into H2 Indicator Supraparticles: Lowering the Limit of Detection by Tuning Incorporated Catalyst Nanoparticles - Zhang, Kailun; Reichstein, Jakob; Groppe, Philipp; Schötz, Simon; Stockinger, Nina; Libuda, Jörg; Mandel, Karl; Wintzheimer, Susanne; Retzer, Tanja (Chemistry of Materials, 2023)
With the increasing interest in H2-based energy storage, H2 detectors gain significant importance. Here, we report on safe, i.e., spark-free, reliable, and highly reactive gasochromic H2 indicator supraparticles (SPs). They are assembled from different types of noble metal nanoparticles (NPs), SiO2 NPs, and the dye resazurin via spray-drying. Their sensing principle is based on the adsorption and activation of H2 on catalytically active noble metal NPs incorporated in the mesoporous supraparticulate framework. Upon stepwise hydrogenation of resazurin molecules with molecular mobility via activated H species, the indicator displays a fast color change visible to the naked eye. We investigate the effect of incorporating different catalytically active NPs into indicator SPs on their sensor performance at different H2 concentrations. We find that the size and material of the catalyst NPs have a strong influence on the sensor response of the H2 indicator as it changes the amount of activated H species available in the system. Enhancing the amount of interstitial H2O in the mesopores of the SPs increases their reaction volume but impairs the reproducibility of their sensor response. Among the studied materials, dispersed Pt NP-containing SPs give the overall best results in terms of overall performance toward H2 detection.<br

Supraparticles for Bare-Eye H2 Indication and Monitoring: Design, Working Principle, and Molecular Mobility - Reichstein, Jakob; Schötz, Simon; Macht, Moritz; Maisel, Sven; Stockinger, Nina; Cuadrado Collados, Carlos; Schubert, Katrin; Blaumeiser, Dominik; Wintzheimer, Susanne; Görling, Andreas; Thommes, Matthias; Zahn, Dirk; et al. (Advanced Functional Materials, 2022)
Indicators for H2 are crucial to ensure safety standards in a green hydrogen economy. Herein, the authors report micron-scaled indicator supraparticles for real-time monitoring and irreversible recording of H2 gas via a rapid eye-readable two-step color change. They are produced via spray-drying SiO2 nanoparticles, AuPd nanoparticles, and indicator-dye resazurin. The resulting gas-accessible mesoporous supraparticle framework absorbs water from humid atmospheres to create a three-phase-system. In the presence of H2, the color of the supraparticle switches first irreversibly from purple to pink and further reversibly to a colorless state. In situ infrared spectroscopy measurements indicate that this color change originates from the (ir)reversible H2-induced reduction of resazurin to resorufin and hydroresorufin. Further infrared spectroscopic measurements and molecular dynamics simulations elucidate that key to achieve this functionality is an established three-phase-system within the supraparticles, granting molecular mobility of resazurin. Water acts as transport medium to carry resazurin molecules towards the catalytically active AuPd nanoparticles. The advantages of the supraparticles are their small dimensions, affordable and scalable production, fast response times, straightforward bare-eye detection, and the possibility of simultaneously monitoring H2 exposure in real-time and ex post. Therefore, H2 indicator supraparticles are an attractive safety additive for leakage detection and localization in a H2 economy.<br
Keywords: hydrogen indicators; hydrogen sensors; in situ DRIFTS measurements; MD simulations; smart additives; supraparticles

Supraparticles for naked‑eye H2 indication and monitoring: improving performance by variation of the catalyst nanoparticles - Zhang, Kailun; Schötz, Simon; Reichstein, Jakob; Groppe, Philipp; Stockinger, Nina; Wintzheimer, Susanne; Mandel, Karl; Libuda, Jörg; Retzer, Tanja (Journal of Chemical Physics, 2023)
The recent transition to H2-based energy storage demands reliable H2 sensors that allow for easy, fast, and reliable detection of leaks. Conventional H2 detectors are based on the changes of physical properties of H2 probes induced by subsurface H-atoms to a material such as electrical conductivity. Herein, we report on highly reactive gasochromic H2 detectors based on the adsorption of H2 on the material surface. We prepared supraparticles (SPs) containing different types of noble metal nanoparticles (NPs), silica NPs, and the dye resazurin by spray-drying and tested their performance for H2 detection. The material undergoes a distinct color change due to the hydrogenation of the purple resazurin to pink resorufin and, finally, colorless hydroresorufin. The stepwise transition is fast and visible to the naked eye. To further improve the performance of the sensor, we tested the reactivity of SPs with different catalytically active NPs by means of in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). We show that the choice of the NP catalyst has a pronounced effect on the response of the H2 indicator. In addition, we demonstrate that the performance depends on the size of the NPs. These effects are attributed to the availability of reactive H-atoms on the NP surface. Among the materials studied, Pt-containing SPs gave the best results for H2 detection.

Thermal Stability and CO Permeability of [C4C1Pyr][NTf2]/Pd(111) Model SCILLs: from UHV to Ambient Pressure - Eschenbacher, Roman; Trzeciak, Simon; Schuschke, Christian; Schötz, Simon; Hohner, Chantal; Blaumeiser, Dominik; Zahn, Dirk; Retzer, Tanja; Libuda, Jörg (Topics in Catalysis, 2023)
Solid catalysts with ionic liquid layers (SCILLs) are heterogeneous catalysts which benefit significantly in terms of selectivity from a thin coating of an ionic liquid (IL). In the present work, we study the interaction of CO with a Pd model SCILL consisting of a 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)-imide ([C4C1Pyr][NTf2]) film deposited on Pd(111). We investigate the CO permeability and stability of the IL film via pressure modulation experiments by infrared reflection absorption spectroscopy (IRAS) in ultrahigh vacuum (UHV) and at ambient pressure conditions by time-resolved, temperature-programmed, and polarization-modulated (PM) IRAS experiments. In addition, we performed molecular dynamics (MD) simulations to identify adsorption motifs, their abundance, and the influence of CO. We find a strongly bound IL wetting monolayer (ML) and a potentially dewetting multilayer. Molecular reorientation of the IL at the interface and multilayer dewetting allow for the accumulation of CO at the metal/IL interface. Our results confirm that co-adsorption of CO changes the molecular structure of the IL wetting layer which confirms the importance to study model SCILL systems under in situ conditions. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-14
Keywords: In Situ; Infrared Spectroscopy; Ionic Liquids; Molecular Dynamics; Permeability; SCILL

Wilkinson-type catalysts in ionic liquids for hydrogenation of small alkenes: understanding and improving catalyst stability - Kratzer, Eva; Schötz, Simon; Maisel, Sven; Blaumeiser, Dominik; Khan Antara, Sharmin; Ewald, Leon; Dotzel, Daniel; Haumann, Marco; Görling, Andreas; Korth, Wolfgang; Jess, Andreas; Retzer, Tanja (Catalysis: Science and Technology, 2023)
In this work, we apply supported ionic liquid phase (SILP) catalysts to hydrogenate 1-alkenes in a continuous fixed-bed reactor. SILP catalyts were prepared using the ionic liquid (IL) 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C4C1Im][NTf2] and tris(triphenylphosphine)rhodium(i) chloride [RhCl(PPh3)3] as a dissolved catalyst. Under isothermal conditions, we observe an increase in activity related to restructuring of the catalyst via formation of supported metal nanoparticles (NPs). Combined in situ infrared spectroscopic and theoretical studies show that NP formation is a step-wise process including the sequential loss of ligands and formation of isolated, supported Rh+-ions as intermediates. To stabilize the highly selective homogeneous catalyst, we systematically vary the experimental conditions (co-feeding of CO) and catalyst design (application of strongly binding CO or chelating xantphos ligand). This knowledge-driven approach results in a stabilization of the molecular Rh complex under hydrogenation conditions.
CRIS-Team Scopus Importer:2023-03-24